SONGKET MOTIF DEVELOPENT OF OGAN ILIR - HESTI ROSITA DWI PUTRI; ACHMAD HALDANI DESTIARMAND (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
Songketis a cultural heritage from the era of the Kingdom of Sriwijaya, songket has aesthetic and philosophical values on each of its motifs or designs. Weaving expertise is passed on from generation to generation using traditional tools, the complicated process of making songket has quite expensive prices. The high demand for songket makes production spread in Ogan Ilir Regency which is a border area with the city of Palembang. Although songket production centers are spread in various regions of Ogan Ilir, these area do not yet have a unique motif, the weavers only follow Palembang’s songket motifs. Making of songket motifs (nyukit) cannot be done by all weavers due to the difficult process, so that the songket motifs are developed very slowly. This research method uses qualitative methods and approaches of people center development toward the songket’s craftsmen of Tanjung Pinang village of Ogan Ilir. This is conducted to find an easier method of making motif structures (menyukit) so that the tradition of making songket motifs can continue to be preserved and developed. The results showed that the most appropriate motifs of Ogan Ilir songket to be simulated was the seluang fish motif.